Environmental Education for Sustainable Development - Arkady Ursul; Tatiana Ursul (International Society of Philosophy and Cosmology, 2018)
The authors believes that by continuing the further roll-out of education for sustainable development (ESD), however, need to start implementing a new strategy for global educational process to accelerate and expand the movement towards "global sustainability". It is shown that the environmental component (and corresponding model) of education currently prevalent in the form of education, which is now called ESD, but this is only the beginning of a formation of a new systemic model of education for sustainable development. For the ecological component of ESD has already added the vision of ESD as a leading education and interpretation education based on the concept of "security through sustainable development."